Pemanfaatan Aksara Incung Sebagai Sumber Pembelajaran Sejarah Lokal dan Pengembangan Jiwa Kewirausahaan Siswa di SMA 4 Kerinci - Rohadatul Nihaliah; Jaihar Aswan Saputra; Glen Rio Sitohang; Desvi Amanda Salsabillah (PT. Hasba Edukasi Mandiri, 2026)
This study aims to explore the potential of the Incung script as a local learning resource and a vehicle for developing an entrepreneurial spirit for students at SMA 4 Kerinci. Using a descriptive qualitative approach, the research was conducted through interviews with history teachers and students, observations of teaching practices, and analysis of curriculum documents and local culture-based entrepreneurial activities. The results indicate that integrating the Incung script into local history learning can increase students' motivation and understanding of Kerinci's cultural heritage, as well as open opportunities for developing creative products based on the Incung script (such as crafts and batik with Incung motifs). This study addresses specific teaching needs, access to entrepreneurship training, and the lack of systematic curriculum integration. The study concludes that utilizing the Incung script as a learning resource and as a basis for entrepreneurship has significant potential for enhancing local history knowledge and Incung-based learning, as well as partnerships with local MSMEs for culture-based entrepreneurship programs.